2021
DOI: 10.1101/2021.11.18.469076
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome and transcriptome architecture of allopolyploid okra (Abelmoschus esculentus)

Abstract: We present the first annotated genome assembly of the allopolyploid okra (Abelmoschus esculentus). Analysis of telomeric repeats and gene rich regions suggested we obtained whole chromosome and chromosomal arm scaffolds. Besides long distal blocks we also detected short interstitial TTTAGGG telomeric repeats, possibly representing hallmarks of chromosomal speciation upon polyploidization of okra. Ribosomal RNA genes are organized in 5S clusters separated from the 18S-5.8S-28S units, clearly indicating an S-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…Previously, there have been controversies about the chromosome number in the okra genome, and the reported okra chromosome number has ranged from 2n = 72 to 2n = 130, based on karyotype analysis [ 21 , 29 ]. In our study, the chromosome number of okra was determined as 2n = 130 by FISH-based karyotype analysis and Hi-C data-assisted chromosome anchoring, which was consistent with previous reports [ 30 , 31 ]. Additionally, a previous study indicated that okra might be a polyploid species [ 30 ], which was validated by our genome assembly and subgenome phasing.…”
Section: Discussionsupporting
confidence: 91%
“…Previously, there have been controversies about the chromosome number in the okra genome, and the reported okra chromosome number has ranged from 2n = 72 to 2n = 130, based on karyotype analysis [ 21 , 29 ]. In our study, the chromosome number of okra was determined as 2n = 130 by FISH-based karyotype analysis and Hi-C data-assisted chromosome anchoring, which was consistent with previous reports [ 30 , 31 ]. Additionally, a previous study indicated that okra might be a polyploid species [ 30 ], which was validated by our genome assembly and subgenome phasing.…”
Section: Discussionsupporting
confidence: 91%
“…KB has united a variety of interactions, such as those between genes and proteins, elements and reactions, medications and illnesses, and organisms and cells (Kanehisa et al 2019 ). Parallel studies were reported in Vatica mangachapoi (Tang et al 2022 ), Hopea hainanensis (Huang et al 2022 ), Neesia altissima (Pratiwi et al 2022 ), C. capsularis (Satya et al 2017 ), Hibiscus hamabo siebold & zuccarini (Wang et al 2021 ), Abelmoschus esculentus (Nieuwenhuis et al 2021 ), Helicoverpa armigera (de la Paz Celorio-Mancera et al 2011 ), Gasterophilus nasalis (Zhang et al 2021 ), and Operculina turpethum (Biswal et al 2021 ). Additionally, GAEV was used to annotate the KO (Iacobas et al 2019 ; Emami-Khoyi et al 2020 ; Nand et al 2020 ; Shah et al 2021 ).…”
Section: Discussionmentioning
confidence: 67%